2013
DOI: 10.1089/jop.2012.0142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olmesartan on Leukocyte Recruitment in Choroid–Sclera Complex in Hypercholesterolemia Model

Abstract: Olmesartan reduced the MCP-1 expression and the resultant macrophage accumulation in the choroid-sclera complex of hypercholesterolemic rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The present study corroborates the findings of earlier studies that hypercholesterolaemia may induce the same events in the choroid–sclera complex. The exacerbated expression of oxidised LDL in the choroid and sclera observed in G1 rabbits could account for the increase in the expression of chemotactic molecules ( 15 ) , such as monocyte chemoattractant protein-1, adhesion molecules ( 16 ) and intercellular adhesion molecule-1, which would induce an increase in macrophage concentrations in the choroid–sclera complex and, consequently, an increase in the thickness of the choroid and sclera as observed in the present study and in other studies ( 16 , 17 , 20 , 48 ) . From the ocular point of view, it is important to note that oxidised LDL, chemotactic molecules, adhesion molecules and macrophages are associated with the physiopathogenesis of AMD and may trigger or worsen this disease ( 2 , 9 , 10 , 46 – 49 ) .…”
Section: Discussionsupporting
confidence: 76%
“…The present study corroborates the findings of earlier studies that hypercholesterolaemia may induce the same events in the choroid–sclera complex. The exacerbated expression of oxidised LDL in the choroid and sclera observed in G1 rabbits could account for the increase in the expression of chemotactic molecules ( 15 ) , such as monocyte chemoattractant protein-1, adhesion molecules ( 16 ) and intercellular adhesion molecule-1, which would induce an increase in macrophage concentrations in the choroid–sclera complex and, consequently, an increase in the thickness of the choroid and sclera as observed in the present study and in other studies ( 16 , 17 , 20 , 48 ) . From the ocular point of view, it is important to note that oxidised LDL, chemotactic molecules, adhesion molecules and macrophages are associated with the physiopathogenesis of AMD and may trigger or worsen this disease ( 2 , 9 , 10 , 46 – 49 ) .…”
Section: Discussionsupporting
confidence: 76%
“…In a recent study, our group showed that olmesartan reduced the expression of MCP-1 and the accumulation of macrophages in the sclera and choroid of hypercholesterolemic rabbits 31. Besides blocking the binding of angiotensin II to the AT1 receptors, olmesartan exerts a mild modulatory activity on PPAR-gamma receptors 32.…”
Section: Discussionmentioning
confidence: 97%
“…This short period has been proven to be sufficient to demonstrate that the serum total cholesterol, triglycerides, HDL cholesterol, and fasting glucose level remained stable and did not interfere with the immunohistochemical analysis of the choroid and sclera. The decision to euthanize rabbits of the NG group after 4 weeks was made based on the results of earlier studies (24,35) . We have demonstrated that cholesterol-enriched diet induces an increase in macrophage concentration in the choroid-sclera com plex, causing thickness of these structures (24,25,35) .…”
Section: Discussionmentioning
confidence: 99%
“…The decision to euthanize rabbits of the NG group after 4 weeks was made based on the results of earlier studies (24,35) . We have demonstrated that cholesterol-enriched diet induces an increase in macrophage concentration in the choroid-sclera com plex, causing thickness of these structures (24,25,35) . The diet also induced hypoxia of the retinal tissue, leading to neuronal damage (35) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation